2022
DOI: 10.1111/rec.13631
|View full text |Cite
|
Sign up to set email alerts
|

Forest restoration by direct seeding: a global bibliometric analysis

Abstract: Direct seeding has been suggested to be a highly cost‐efficient system for forest restoration but is still not applied on a large scale worldwide. Thus, to improve the knowledge surrounding the application of this system, I conducted a global bibliometric analysis about forest restoration by direct seeding. Based on a literature search of three online databases (Web of Science, Scopus, and Google Scholar), I found 81 peer‐reviewed articles related to field experiments testing direct seeding for forest restorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Reynolds et al (2013) reported that seed‐based restoration of an eelgrass provided abundant propagules, rapidly increased coverage over 1600 ha in 10 years, and improved GD in recovered populations. However, direct seeding, a cost‐effective and time‐efficient restoration practice, has not yet been widely adopted throughout the world and should be advocated in the future with appropriate source populations (Leverkus et al, 2021; Souza, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Reynolds et al (2013) reported that seed‐based restoration of an eelgrass provided abundant propagules, rapidly increased coverage over 1600 ha in 10 years, and improved GD in recovered populations. However, direct seeding, a cost‐effective and time‐efficient restoration practice, has not yet been widely adopted throughout the world and should be advocated in the future with appropriate source populations (Leverkus et al, 2021; Souza, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The United Nations classifies forests according to their climatic domain as tropical, boreal, temperate, and subtropical forests, covering approximately 45, 27, 16, and 11% of the total area, respectively (FAO 2020). Each type of forest has unique levels of biodiversity, vegetation structures, and ecological processes that need to be considered in the restoration process (de Souza 2022).…”
Section: Discussionmentioning
confidence: 99%
“…They also play a pivotal role in global carbon dynamics, accounting for a third of terrestrial gross primary production and half of the carbon stored in land (Hubbell et al 1999). However, they are also the most deforested forest landscapes (FAO 2020; de Souza 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The records were downloaded and saved as plain text format by selecting the export format “full records and cited references”, and then imported into VOSviewer (version 1.6.18, 2022, Leiden University, Leiden, the Netherlands) for further citation analysis. The impact factors (IF 2021 and 5-year IF) for the identified journals were taken from the Journal Citation Report (JCR 2021) that was updated at the end of June 2022 (Clarivate, Journal Citation Reports ™ 2021, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Bibliometric technique has been adopted to analyse several subjects covering Web of Science category of Ecology. Of such topics, the following could be mentioned among others: research trends in bat echolocation studies between 1970 and 2021 (Cao et al 2022), alpine treelines as ecological indicators of global climate change (Chen et al 2022), applying network analysis to explore the global scientific literature on food security (Skaf et al 2020), bibliometric analysis of human–wildlife conflict (Su et al 2022), ecological compensation and its application in land resources (Zhang et al 2021), ecological network analysis 2010–2016 (Borrett et al 2018), ecosystem services in Southern Africa (Nyathi et al 2022), evolution of the field of ecological restoration over the last three decades (Guan et al 2019), forest restoration by direct seeding (de Souza 2022), global biodiversity research during 1900–2009 (Liu et al 2011), global trends in zooplankton research of freshwater ecosystems during 1991–2020 (Gao et al 2022), landscape of ecological research in Australia (Kumar and Khormi 2013), and many others.…”
Section: Introductionmentioning
confidence: 99%